Exploring the anatomy of Linguatula serrata using micro-computed tomography - Alice Birckhead; Ryan O'Hare Doig; Ann Carstens; David Jenkins; Shokoofeh Shamsi (International Journal for Parasitology: Parasites and Wildlife, 2024)
Micro-computed tomography (micro-CT) is an emerging tool in parasitology that can assist in analysing morphology and host-parasitic interactions. It is a non-destructive, cross-sectional imaging technique that offers good resolution and the ability to create three-dimensional (3D) reconstructions. Here, we used micro-CT to study Linguatula serrata, which is a zoonotic pentastome parasite that infects dogs and ruminants throughout the world. The aims of this study were to describe the internal and external anatomy of adult L. serrata specimens using micro-CT, and to describe and compare specimens stained with 0.3% phosphotungstic acid (PTA) and 1% iodine (I2). Ten adult L. serrata specimens were subjected to micro-CT examination. The specimens were fixed in 70% ethanol and stained with 0.3% PTA or 1% I2. Both stains offered good tissue contrast. The main identifying external features of L. serrata (hooks, mouth, buccal cadre) were clearly visible. Virtual sections and 3D reconstructions provided a good overview of the coelomic cavity, with visualisation of the digestive tract, nervous system, and male and female reproductive organs. These micro-CT images and morphological descriptions may serve as an anatomical reference for L. serrata, in particular, the internal anatomy which has not been described in recent years.